EFFORTS TO TRAIN THE CHARACTER OF STUDENTS BY USING THE COOPERATIVE LEARNING MODEL TYPE GI (GROUP INVESTIGATION) IN SCIENCE LEARNING - Santoso, Agus (Science Education and Application Journal, 2019)
Education up to now is considered as a medium to build knowledge as well as the personality of children to become better human beings, so positive learning must be instilled in learning. Planting characters can be realized through cooperative learning type group investigation. This research is to overcome learning problems in class related to the character of social care, environmental care, responsibility, and cooperation. This research was conducted in two cycles, using a characteristic behavior observation sheet instrument. Descriptive data analysis by looking at the increase in the percentage of character behavior in students. The implementation of learning in the first cycle is 94% and the second cycle is 100%. Based on the results of observations in the first and second cycles there are positive character developments in students heading in a better direction than before. To build a positive character of character training students need to be carried out continuously so that their development is increasing and entrenched.